High elastic modulus glass composition and application

By introducing components such as CaO, TiO2 and Li2O into SiO2-Al2O3-MgO system glass, a new high-elastic modulus glass composition is formed, which solves the problems of increasing density and preparation difficulty of existing high-modulus glass materials, and achieves high-modulus, low-density and high-temperature stability of glass materials, suitable for large-scale production and lightweight design.

CN119841548APending Publication Date: 2025-04-18EAST CHINA UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510054664.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

While increasing the modulus, existing high-modulus glass materials increase density, deterioration of other mechanical properties and increased production difficulty, affecting the large-scale production and lightweight potential of materials.

Method used

By introducing components such as CaO, TiO2 and Li2O into SiO2-Al2O3-MgO system glass, the weight percentage content is adjusted to form a new high elastic modulus glass composition, which meets the high modulus, low density and suitable viscosity characteristics.

Benefits of technology

The glass materials with high modulus, low density and high temperature stability are achieved, which reduces the melting temperature and wire drawing temperature, improves the production efficiency and lightweight potential of the material, and is suitable for large-scale production and subsequent wire drawing processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a glass composition with high elastic modulus. The glass composition is prepared from the following components in percentage by weight: 45.0 to 60.0 percent of SiO2, 22.0 to 35.0 percent of Al2O3, 0 to 3.0 percent of CaO, 10.0 to 16.0 percent of MgO, 2.0 to 8.0 percent of TiO2, 0.10 to 0.25 percent of Li2O, not zero of CaO and 10.0 to 16.0 percent of CaO + MgO. The glass product taking the components as the main raw materials has the elasticity modulus of 95-100Gpa, the specific modulus of 3.60 * 107-3.82 * 107 m < 2 > / s < 2 >, the thermal expansion coefficient of 2.40-3.40 ppm / DEG C and the bending strength of 120-160Mpa, has the characteristics of high elasticity modulus and high specific modulus, and is suitable for the fields of large wind blades, aerospace, automobile manufacturing, electronics and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of engineering glass, and in particular relates to a high elastic modulus glass composition and application thereof. Background Art

[0002] High elastic modulus glass materials have shown broad application potential in many product fields such as wind power generation, automobile manufacturing, aerospace, electronics and electrical appliances due to their high strength, light weight, high modulus, good corrosion resistance and high temperature resistance. These characteristics of high elastic modulus glass materials not only promote the lightweight design of products, but also significantly improve the overall performance and service life of products, indicating that this type of material has extremely broad market application prospects.

[0003] SiO2-Al2O3-MgO system glass, as an important type of high modulus glass material, has excellent mechanical strength and chemical stability, but its high melting temperature, high melt viscosity, bubble removal difficulties caused by high melting temperature, and high drawing temperature inevitably push up the production cost of high modulus glass materials, becoming a bottleneck restricting its large-scale production. Current research focuses on improving mechanical properties by doping with trace oxides (such as lithium oxide, boron oxide, cerium oxide, zirconium oxide, etc.) and rare earth oxide modification (such as lanthanum oxide and yttrium oxide). However, in the process of realizing the present invention, the inventors found that there are at least the following problems in the prior art: while the above-mentioned modification strategy improves the modulus, it is often accompanied by an increase in density, a reduction in other mechanical properties, and an increase in the difficulty of preparation, which affects the large-scale production and lightweight potential of the material. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a high elastic modulus glass composition and its application in view of the deficiencies of the above-mentioned prior art.

[0005] In order to solve the above technical problems, on the one hand, a high elastic modulus glass composition is provided, comprising the following components in weight percentage: SiO2 45.0-60.0wt%, Al2O3 22.0-35.0wt%, CaO 0-3.0wt%, MgO10.0-16.0wt%, TiO2 2.0-8.0wt%, Li2O 0.10-0.25wt%, wherein the weight percentage of CaO is not zero, CaO+MgO 10.0-16.0wt%. The composition design requirements of high modulus glass or high modulus glass fiber are met, and a new high modulus glass material having high modulus, low density and suitable viscosity characteristics, high specific modulus and suitable for large-scale production and subsequent wire drawing processing can be obtained.

[0006] On the other hand, a high elastic modulus glass composition product comprising the above composition is provided, wherein the product comprises glass or glass fiber, has an elastic modulus of 95 to 100 GPa, and a density of 2.60 to 2.70 g / cm 3 , the specific modulus is 3.60×10 7 ~3.82×10 7 m 2 / s 2 , thermal expansion coefficient is 2.40~3.40ppm / ℃, bending strength is 120~160Mpa. The above glass products have the characteristics of high modulus, low density and high temperature stability, and have the advantages of low melting temperature, low energy consumption and high production efficiency; among them, glass fiber with the above characteristics of high modulus, low density and high temperature stability has high structural rigidity and light weight, providing an ideal material for lightweight product design in many fields such as wind power generation, automobile manufacturing, aerospace, and electronic appliances.

[0007] On the other hand, a method for preparing the above-mentioned glass fiber is provided, wherein the raw material comprises the above-mentioned glass composition, the drawing temperature is 1300-1390°C, and the components designed with the above-mentioned ingredients are used as raw materials, the molding temperature is lower, and the drawing process requirements are met. Glass fibers with higher comprehensive performance can be obtained with high efficiency, low equipment requirements, and low cost, achieving a balance between performance and efficiency, and facilitating industrial-scale production.

[0008] Compared with the prior art, the present invention has the following advantages:

[0009] 1. The present invention provides a high elastic modulus glass composition that meets the component design requirements of high modulus glass or high modulus glass fiber, and can obtain a new type of high modulus glass material that has high modulus, low density and suitable viscosity characteristics, has a high specific modulus and is suitable for large-scale production and subsequent wire drawing processing.

[0010] 2. The present invention provides a product comprising the above composition, including glass or glass fiber, with an elastic modulus of 95 to 100 GPa and a density of 2.60 to 2.70 g / cm 3 , the specific modulus is 3.60×10 7 ~3.82×10 7 m 2 / s 2 The thermal expansion coefficient is 2.40-3.40ppm / ℃, taking into account both high elastic modulus and high specific modulus.

[0011] 3. Preferably, the present invention provides a glass fiber containing the above components, which has the characteristics of high modulus, low density and high temperature stability, has high structural rigidity and light weight, and provides an ideal material for the design of lightweight products in many fields such as wind power generation, automobile manufacturing, aerospace, and electronic appliances.

[0012] The technical solution of the present invention is further described in detail below in conjunction with embodiments. DETAILED DESCRIPTION

[0013] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0014] In the following description, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural.

[0015] In the following description, the terms "include", "comprising", "having" and "containing" are open-ended terms, meaning including but not limited to.

[0016] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0017] Those skilled in the art will appreciate that the numerical ranges in the embodiments of the present application are to be understood as each intermediate value between the upper and lower limits of the scope also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.

[0018] Unless otherwise stated, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art in the field described in the present application. Although the present application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0019] On the one hand, a high elastic modulus glass composition is provided, comprising the following components in weight percentage: SiO2 45.0-60.0wt%, Al2O3 22.0-35.0wt%, CaO 0-3.0wt%, MgO 10.0-16.0wt%, TiO2 2.0-8.0wt%, Li2O 0.10-0.25wt%, wherein the weight percentage of CaO is not zero, CaO+MgO 10.0-16.0wt%. The sum of the weight percentages of the components is 100%, which specifically solves the defects of the current high elastic modulus glass having high density and low specific modulus.

[0020] The components of high elastic modulus glass are mainly SiO2-Al2O3-MgO system, and the modulus is usually around 90-93Gpa. SiO2 is a glass network former and the main component of the glass skeleton. This component and its content are the main factors affecting the mechanical strength of glass. The addition of MgO and Al2O3 helps to improve the elastic modulus.

[0021] As an important alkali metal oxide, CaO has high hardness and certain mechanical strength. The inventors found that CaO can improve the molding characteristics and mechanical and chemical stability of glass, and affect the melting temperature and melt fluidity of glass. During the experiment, the inventors found that when CaO and MgO are introduced at the same time and the weight proportion of CaO and MgO in the glass composition is controlled to be 10.0-16.0wt%, the mechanical properties and chemical stability of the glass can be significantly improved. Compared with glass without CaO, the elastic modulus is significantly improved, and the drawing temperature is significantly reduced. The comprehensive performance of glass transparency, high temperature resistance and fluidity can be improved. When the total content of CaO and MgO is greater than 16.0wt%, crystals are precipitated during the cooling process of the glass melt, and the transparency and high temperature resistance are reduced. When the total content is less than 10.0wt%, the glass viscosity increases, the fluidity of the glass melt at high temperature is reduced, and the molten glass liquid is turbid.

[0022] TiO2 has three main crystal forms, anatase, rutile and brookite, which can transform into each other. TiO2 is usually considered as an intermediate oxide component. During the glass forming process, the crystal phase will change, which will affect the three-dimensional network of the glass. For example, due to the nucleation characteristics of TiO2, it is very likely to cause the glass structure to change during the melt forming process, and phase change processes such as crystallization will occur. Therefore, the addition of TiO2 is usually limited or its addition amount is strictly controlled, such as limiting its addition amount to no more than 2wt%. The inventor unexpectedly found that the addition of an appropriate amount of TiO2 can reduce the high-temperature viscosity of the glass. If its content is less than 2.0wt%, it cannot significantly improve the chemical resistance of the glass. When the content is higher than 8.0wt%, it will cause the glass to separate into phases, causing the glass to be dark yellow and reduce transparency. At the same time, it will increase the melting temperature of the glass, making it more difficult to form.

[0023] Li2O has high thermal shock resistance. The inventors found that an appropriate amount of Li2O can reduce the melting temperature and thermal expansion coefficient of glass. When the content exceeds 0.25wt%, the mechanical properties of the glass decrease. When the addition amount is between 0.10-0.25wt%, the bending strength can be improved and the T3 temperature can be reduced.

[0024] It is generally believed that SiO2 is a glass network former and the main oxide that forms the glass skeleton, while Al2O3, as a network exosome, is mostly used as a glass skeleton doping component, and its addition amount often does not exceed 1 / 3 of SiO2. The inventors found that when the SiO2 content is greater than 60.0wt%, the melting temperature and softening temperature of the glass will be too high, causing the glass to produce thermal stress under large temperature changes, which has a negative impact on stability. When the SiO2 content is less than 45.0wt%, the thermal expansion coefficient of the glass will increase. When the Al2O3 content is greater than 35.0wt%, the viscosity of the glass will increase, making the preparation of the glass difficult, and the risk of glass crystallization will also increase. If the Al2O3 content is less than 22.0wt%, the elastic modulus of the glass will be reduced, resulting in a significant decrease in the mechanical strength of the glass. The inventors also found that by introducing a large amount of Al2O3 into the SiO2 glass network, it helps to promote its interaction with the silicon oxygen network, exert a synergistic effect between the two, and promote the formation of an aluminum oxide network with higher structural stability and stronger mechanical properties. That is, when the weight ratio of Al2O3 to SiO2 is 0.4-0.7, it can be successfully formed, and the elastic modulus and specific modulus can be improved on the basis of controlling the drawing temperature.

[0025] In the field of high modulus glass, rare earth oxides are generally considered to be effective components for improving modulus, and are widely used in the field of high modulus glass due to their ability to prevent or reduce crystal formation and growth. The glass formula of the present invention can reduce the melting temperature and viscosity without adding rare earth oxide components, and realize the large-scale production of high mechanical properties and lightweight glass.

[0026] Based on the above content, it can be seen that Al2O3, TiO2 and MgO all have a positive effect on the improvement of the elastic modulus of glass. The inventors found that when the sum of the weight percentages of Al2O3+TiO2+MgO ​​is less than 40%, the glass is easy to burn, but the elastic modulus is significantly reduced. When the sum of the weight percentages of the three is between 40% and 51%, glass products with high elastic modulus and high mechanical properties can be obtained under lower drawing temperature conditions.

[0027] The present invention has been subjected to a series of experiments before the application is filed. A part of the experimental results are listed here to further describe the invention in detail, and the following is a detailed description in conjunction with the embodiments.

[0028] Example 1

[0029] This embodiment provides a high elastic modulus glass composition, the components of which are shown in Table 1.

[0030] This embodiment provides a method for preparing glass using the above composition as a raw material, comprising:

[0031] The above composition is mixed and placed in a platinum-rhodium crucible, and the platinum-rhodium crucible containing the composition is placed in a lifting furnace and heated from room temperature to 1550° C. for 4 hours to obtain a clear and transparent glass liquid;

[0032] The glass liquid is poured into a graphite mold to obtain a bulk glass sample, and the graphite mold containing the bulk glass sample is placed in a muffle furnace at 550° C. and kept warm for 4 hours for annealing to obtain a high elastic modulus glass;

[0033] The glass was cut into the size of the sample to be tested to obtain the sample to be tested, and the elastic modulus, bending strength, thermal expansion coefficient, density and viscosity temperature of the sample to be tested were tested. The results are shown in Table 1.

[0034] This embodiment provides a method for preparing glass fiber using the above composition as a raw material, comprising:

[0035] The above composition is mixed and then placed in a kiln at 1550°C for melting to obtain a clear and homogenous molten liquid;

[0036] The molten liquid is placed on a Pt drain plate, stretched at high speed by a wire drawing machine, and wound in a certain direction to obtain glass fibers.

[0037] Embodiments 2 to 7

[0038] The composition components in the above embodiments are shown in Table 1, and the method for preparing glass or glass fiber is the same as that in Embodiment 1.

[0039] Comparative Examples 1 to 7

[0040] The above comparative examples are for examining the influence of component changes in the corresponding embodiments on the properties of glass and glass fiber, wherein in comparative example 1, the SiO2 content exceeds 60wt%, the Al2O3 content is less than 22wt%, Al2O3 / SiO2 is less than 0.4, and the sum of the Al2O3+TiO2+MgO ​​contents is less than 40%; in comparative example 2, the SiO2 content is less than 45wt%, the Al2O3 content exceeds 35wt%, Al2O3 / SiO2 is greater than 0.7, and the sum of the Al2O3+TiO2+MgO ​​contents is greater than 51%; in comparative example 3, the CaO content is 0; in comparative example 4, the CaO content is greater than 3.0wt%; in comparative example 5, the TiO2 content exceeds 8.0wt%; in comparative example 6, the TiO2 content is less than 2wt%; and comparative example 7 does not contain Li2O.

[0041] The ingredients of the compositions in each comparative example are shown in Table 2, and the preparation method is the same as that of Example 1.

[0042] Table 1 Composition and properties of glass of Examples 1 to 7

[0043]

[0044] Among them, the specific modulus is the ratio of the elastic modulus of the material to its density, defined as: specific modulus = elastic modulus / density. The elastic modulus is measured by the pulse excitation method, and the density is measured by the Archimedes drainage method. The thermal expansion coefficient is measured by a thermal expansion instrument (DIL), and the flexural strength is measured by a universal testing machine using a three-point bending method. The high-temperature viscosity test is tested by the American BROOKFIELD rotary high-temperature viscometer, where the temperature T3 corresponding to 1000 poise is the temperature corresponding to the glass viscosity equal to 1000 poise, that is, the drawing temperature or T3 temperature.

[0045] According to Table 1, the elastic modulus of the glass of the present invention is 95-100 GPa, and the density is 2.60-2.70 g / cm 3 , the specific modulus is 3.60×10 7 ~3.82×10 7 m 2 / s 2 , thermal expansion coefficient is 2.40-3.40 ppm / °C, bending strength is 140-160 MPa, and T3 is 1300-1390°C. The glass fiber properties of the corresponding embodiment are basically consistent with the glass properties.

[0046] Table 2 Composition and properties of glass of comparative examples 1 to 7

[0047]

[0048] From the comparative examples and embodiments, it can be seen that when the SiO2 content exceeds 60% and the Al2O3 content is lower than 22.0%, Al2O3 / SiO2 is less than 0.4 and the sum of the Al2O3+TiO2+MgO ​​contents is lower than 40%, the elastic modulus and specific modulus of the glass are reduced, while the viscosity temperature value is increased. When the SiO2 content is less than 45% and the Al2O3 content exceeds 35%, Al2O3 / SiO2 is greater than 0.7 and the sum of the Al2O3+TiO2+MgO ​​contents is greater than 51%, the high-temperature viscosity of the glass increases after melting, making the molding operation difficult.

[0049] When CaO is not included, the elastic modulus of the glass decreases and the T3 temperature increases by nearly 20° C. When the CaO content is greater than 3.0 wt %, the elastic modulus of the glass decreases.

[0050] When the TiO2 content exceeds 8.0wt%, the T3 temperature of the glass increases by nearly 30°C, the bending strength decreases by 20Mpa, and the color of the glass is too dark and the transparency becomes poor. When the TiO2 content is less than 2wt%, the elastic modulus of the glass decreases.

[0051] When Li2O is not added, the bending strength of the glass decreases and the T3 temperature increases significantly.

Claims

1. A high elastic modulus glass composition, characterized in that: The invention comprises the following components in percentage by weight: SiO2 45.0-60.0wt%, Al2O3 22.0-35.0wt%, CaO 0-3.0wt%, MgO10.0-16.0wt%, TiO2 2.0-8.0wt%, Li2O 0.10-0.25wt%, wherein the percentage by weight of CaO is not zero, and CaO+MgO is 10.0-16.0wt%.

2. The high elastic modulus glass composition according to claim 1, characterized in that: The invention comprises the following components in percentage by weight: SiO2 47.0-58.0wt%, Al2O3 24.0-34.0wt%, CaO 0.5-3.0wt%, MgO 12.0-14.0wt%, TiO2 2.5-6.5wt%, and Li2O 0.10-0.25wt%.

3. The high elastic modulus glass composition according to claim 2, characterized in that: CaO+MgO 13.0~15.0wt%.

4. The high elastic modulus glass composition according to claim 1, characterized in that: The sum of the weight percentages of the following components: Al2O3+TiO2+MgO ​​is 40-51wt%.

5. The high elastic modulus glass composition according to claim 1, characterized in that: The weight percentage ratio of the following components Al2O3 / SiO2 is 0.4 to 0.

7.

6. A high elastic modulus glass composition product, characterized in that: The invention comprises a high elastic modulus glass composition as claimed in any one of claims 1 to 5; the elastic modulus of the high elastic modulus glass composition product is 95 to 100 GPa, and the density is 2.60 to 2.70 g / cm 3 , the specific modulus is 3.60×10 7 ~3.82×10 7 m 2 / s 2 The thermal expansion coefficient is 2.40~3.40ppm / ℃ and the flexural strength is 120~160Mpa.

7. The high elastic modulus glass composition product according to claim 6, characterized in that: The high elastic modulus glass composition product includes glass or glass fiber.

8. A method for preparing a high elastic modulus glass composition product as claimed in claim 7, characterized in that: The drawing temperature of the prepared glass fiber is 1300-1390°C.

9. A composite material, characterized in that: Comprising the glass fiber as claimed in claim 7.

Citation Information

Patent Citations

  • Glass composition

    CN108083631A

  • Optical glass

    CN110818250A

  • High performance fiber glass composition with improved specific modulus

    CN111217531A

  • Glass composition

    CN114920453A

  • Glass fiber and composition for glass fiber

    WO2024106292A1